A Comparison between Endodontics and Implantology: An 8‐Year Retrospective Study. (14th November 2011) - Vozza, Iole; Barone, Antonio; Quaranta, Manlio; De Paolis, Gianfranco; Covani, Ugo; Quaranta, Alessandro
ABSTRACT Purpose: The aim of this study was to compare endodontic and implant treatments and to evaluate their predictability over an 8‐year period on the basis of an analysis of survival data and a retrospective clinical study. Materials and Methods: A group of 40 partially edentulous patients were selected for this study. Their teeth had been endodontically treated and rehabilitated using gold alloy and ceramic restorations. In these patients, 65 osseointegrated implants were restored with single gold alloy–ceramic crowns and monitored on a yearly basis for 8 years with standardized periapical radiographs, using a polivynilsiloxane occlusal key as a positioner. A total of nine patients who did not attend the yearly follow‐up were excluded from the study. The Melloning and Triplett criteria were used to evaluate the clinical results obtained in the implant sites. The clinical results of the 56 endodontically treated teeth, restored with the fixed prosthesis of 40 patients, were analyzed according to probing depth as well as an assessment of the correct apical and coronal seals. The survival rate was calculated using the Kaplan–Meier method and the statistical significance was calculated using the chi‐square test. Results: During the follow‐up of the endodontically treated elements, seven failures were detected (83.34%) and the success rate of implants inserted in the same patients was equal to 80.8%, with nine implants lost in 8 years. The survival analysis of the elements treated with both therapies was not statistically significant (p = .757) and the confidence interval was between 0.2455 and 2.777. Conclusion: In view of the superimposable results between the two therapies, it should be noted that the endodontically treated teeth could be interested by different pathologies while the restoration of the atrophic edentulous ridge with an implant support is predictable when patients comply with correct oral hygiene and when the occlusal loads are axially distributed in implant‐protected occlusion.